THE INFLUENCE OF INTERNAL FACTORS OF PREGANT WOMEN ON TRIPLE ELIMINATION EXAMINATION - Shuviatul Chasanah; Linda Dewanti; Wahyul Anis (UNIVERSITAS AIRLANGGA, 2021)
AbstractBackground: HIV, Hepatitis dan Syphilis can be transmitted from mother to fetus which causes high morbidity dan mortality, especially in developing countries. Transmission of this infection can be prevented by early detection of triple elimination during pregnancy to the maximum. Optimizing the scope of the examination through the identification of internal factors that influence pregnant women to perform triple elimination examination Methods: This study is a descriptive analytic study with a cross sectional approach. The number of samples was 69 pregnant women at Poli KIA Puskesmas who had never done a triple elimination examination. Sampling with accidental sampling. The independent variable of the study was the mother's internal factors consisting of the mother's socio-economic characteristics, knowledge, attitudes dan motivation. The dependent variable is the willingness of pregnant women to perform triple elimination examination. Analysis using the Mann Whitney test, significant if the difference in p-value <0.05. Result : From 69 respondents, 13 mothers were not willing to do the examination. The internal factors of pregnant women have a different average between those who are willing dan unwilling, but the difference is not significant (> 0.05) dan has no influence on the mother's decision to perform a triple elimination examination. The P-value of each factor was obtained from characteristics dan socio-economic characteristics (age (0.550), education (0.602), gravida (0.829), gestational age (0.612), family type (0.567), number of family members (0.407), mother's occupation (0.886 ), husbdan's occupation (0.761), income (0.733), knowledge (0.311), motivation (0.281), dan attitude (0.714) Conclusion: There is no internal factor of the mother that affects the willingness to perform triple elimination examination during pregnancy, further research is needed on external factors from pregnant women to maximize the coverage of triple elimination examination